Invasive Fusobacterium necrophorum Disease in a Patient With Postpartum Bacteremia and Muscle Abscess. Issue 4 (July 2015) - Scott, Shannon; Carlan, S. J.; Busowski, Mary; Wilson, Jack; Madruga, Mario
<x xml:space="preserve">Abstract</x> Abstract Fusobacterium necrophorum is a gram-negative anaerobe that can be the primary pathogen in local or systemic infectious disease. Fusobacterium necrophorum subspecies necrophorum is a biovar considered to be mainly of animal origin not classically implicated in human disease. A healthy 20-year-old woman delivered a term infant vaginally without complications. She returned 13 days postpartum with septicemia-positive blood cultures for F. necrophorum subspecies necrophorum. She developed a lung infiltrate piriformis muscle abscess that responded rapidly to intravenous antibiotic treatment. Fusobacterium necrophorum subspecies necrophorum can be the etiologic agent in postpartum invasive disease with septic embolization.